Photoinhibition of photosystem I under high light in the shade-established tropical tree species Psychotria rubra - Huang, Wei; Zhang, Shi-Bao; Zhang, Jiao-Lin; Hu, Hong (Frontiers in Plant Science, 2015)
The photosynthetic sensitivity to high light differs among understory plants of shade- and sun- established tree species. Shade-established tree species are sensitive to high light but the underlying photosynthetic mechanism has not been fully resolved. In the present study, we examined the responses of photosystem I (PSI) and photosystem II (PSII) to high light in shade leaves of a shade-established tree species Psychotria rubra and a sun-established tree species Pometia tomentosa. After exposure to 2000 μmol photons m−2 s−1 for 2 h, the maximum photo-oxidizable P700 (Pm) decreased by 40% and 9% in P. rubra and P. tomentosa, respectively. These results indicate that the shade-established species P. rubra is incapable of protecting PSI under high light. Strong photoinhibition of PSII under high light led to large depression of electron transfer from PSII to PSI and then prevented further photodamage to PSI. During the high light treatment of 2000 μmol photons m−2 s−1, PSI photoinhibition in P. rubra was accompanied with high levels of cyclic electron flow (CEF) and P700 oxidation ratio. Therefore, we propose that PSI photoinhibition under high light in P. rubra is dependent on electron transfer from PSII to PSI, and CEF is unlikely to play a major role in photoprotection for PSI in P. rubra. These findings suggest that photoinhibition of PSI is another important mechanism underlying why shade-established species cannot survive under high light.